PENDIDIKAN ISLAM PADA MASA KHULLAFAH RASYIDIN SERTA PERANANNYA DALAM PENGEMBANGAN PENDIDIKAN - Juandi Pasaribu; Muhammad Zalnur; Zulmuqim Zulmuqim (Tazkiya: Jurnal Pendidikan Islam, 2024)
The purpose of this writing is to examine in more depth the history of Islamic education before, and during the time of Khulafaur Rasyidin. This research uses critical historical methods through literature studies using a historical approach which specifically uses the following steps: First, heuristics are activities of searching, collecting, categorizing and researching historical sources; Second, source criticism is the activity of testing historical sources using external and internal criticism; Third, interpretation is the activity of interpreting facts that have been tested with source criticism; Fourth, presentation by conveying the synthesis obtained in a historical work. The results of this research show that Islamic education during the time of the Prophet was implemented in two periods, namely the Mecca and Medina periods. Education during the Mecca period was carried out, namely the secret stage, the overt stage and the public appeal stage. Meanwhile, education during the Medina period was a continuation of education in Mecca, namely the formation and development of a new society. Islamic education at this time was divided into four periods, namely: the Caliph Abu Bakr as-Siddiq period, the Umar bin Khatab period, the Usman bin Affan period and the Ali bin Abu Talib period.Keywords: Khulafaur Rasyidin, leader, Tauhid education